How Sensory Experience and Store Layout Navigation Shape Unplanned Buying Behavior? An Empirical Study of Hokky Supermarket Citraland Surabaya - Diah Darmayanti (Journal of Economics and Management Scienties, 2026)
This study examines the influence of sensory experience and layout & navigation on unplanned buying behavior, with psychological reward as a mediating mechanism among consumers of Hokky Supermarket Citraland Surabaya. Based on the Stimulus-Organism-Response (S-O-R) framework, sensory experience and layout & navigation are conceptualized as environmental stimuli, psychological reward as the organismic state, and unplanned buying behavior as the behavioral response. A quantitative explanatory approach was employed using survey data from 423 consumers with shopping experience at Hokky Supermarket Citraland Surabaya. Structural Equation Modeling (SEM) was applied to evaluate the measurement model and test direct and indirect relationships. The results support all seven proposed hypotheses. Sensory experience and layout & navigation positively affect psychological reward and directly influence unplanned buying behavior. Psychological reward also exerts the strongest direct effect on unplanned buying behavior while significantly mediating the relationships between both environmental factors and buying behavior. These findings reinforce the S-O-R framework by demonstrating that supermarket environmental stimuli influence consumer behavior both directly and indirectly through positive psychological states. The study contributes to retail consumer behavior literature by integrating environmental and psychological factors within the context of an Indonesian local supermarket and offers practical insights for enhancing consumer purchasing behavior through store environment design.